High-Frequency Oscillatory Ventilation and Ventilator-Induced Lung Injury: Size Does Matter. Issue 1 (January 2020) - Herrmann, Jacob; Lilitwat, Weerapong; Tawhai, Merryn H.; Kaczka, David W.
Abstract : Objectives: The theoretical basis for minimizing tidal volume during high-frequency oscillatory ventilation may not be appropriate when lung tissue stretch occurs heterogeneously and/or rapidly. The objective of this study was to assess the extent to which increased ventilation heterogeneity may contribute to ventilator-induced lung injury during high-frequency oscillatory ventilation in adults compared with neonates on the basis of lung size, using a computational model of human lungs. Design: Computational modeling study. Setting: Research laboratory. Subjects: High-fidelity, 3D computational models of human lungs, scaled to various sizes representative of neonates, children, and adults, with varying injury severity. All models were generated from one thoracic CT image of a healthy adult male. Interventions: Oscillatory ventilation was simulated in each lung model at frequencies ranging from 0.2 to 40 Hz. Sinusoidal flow oscillations were delivered at the airway opening of each model and distributed through the lungs according to regional parenchymal mechanics. Measurements and Main Results: Acinar flow heterogeneity was assessed by the coefficient of variation in flow magnitudes across all acini in each model. High-frequency oscillatory ventilation simulations demonstrated increasing heterogeneity of regional parenchymal flow with increasing lung size, with decreasing ratio of deadspace to total acinar volume, and with increasing frequency above lung corner frequency and resonant frequency. Potential for resonant amplification was greatest in injured adult-sized lungs with higher regional quality factors indicating the presence of underdamped lung regions. Conclusions: The potential for ventilator-induced lung injury during high-frequency oscillatory ventilation is enhanced at frequencies above lung corner frequency or resonant frequency despite reduced tidal volumes, especially in adults, due to regional amplification of heterogeneous flow. Measurements of corner frequency and resonant frequency should be considered during high-frequency oscillatory ventilation management. Abstract : Supplemental Digital Content is available in the text.